Anti-Sarcopenic Obesity Effects of Lonicera caerulea Extract in High-Fat Diet-Fed Mice - You-Suk Lee; Eun-Jung Park; Sung-Min Kim; Jong-Yeon Kim; Hae-Jeung Lee (MDPI AG, 2021)
Sarcopenic obesity is a combination of sarcopenia and obesity. Although several herbal extracts showed improvement on sarcopenia and obesity, respectively, there are few studies on sarcopenic obesity. Lonicera caerulea (honeysuckle berry, HB) can ameliorate metabolic disorders including obesity. However, its effects on sarcopenic obesity have not been reported yet. Thus, the aim of this study was to investigate whether HB extract might have any beneficial effects on sarcopenic obesity in high-fat diet-induced mice. Forty-eight mice were classified into six groups and treated for eight weeks: (1) NC, normal diet control; (2) HC, high-fat diet control; (3) PC, high-fat diet with orlistat; (4) HB100, high-fat diet with HB extract at 100 mg/kg; (5) HB200, high-fat diet with HB extract at 200 mg/kg; and (6) HB400, high-fat diet with HB extract at 400 mg/kg. Body weight, fat accumulation, muscle mass, muscle strength, and mRNA expression of muscle atrophy were monitored. Compared with the HC group, HB administration showed anti-obesity properties. It reduced body weight gain and modulated serum biochemical parameters and tissue antioxidant enzymes. HB also increased muscle strength and muscle mass of hind legs. In addition, it decreased mRNA expression levels of Atrogin1 and MuRF1 as markers of muscle atrophy but increased PGC1α and SIRT1 as markers of muscle growth. These results suggest that HB might be effective in preventing sarcopenia associated with obesity.